Oil Palm Empty Bunches Bioconversion Using Trichoderma sp. and Black Soldier Fly Larvae As Poultry Feed Composition - Mujahid, Mujahid; Amin, A. A.; Hariyadi, Hariyadi; Fahmi, M. R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
Empty Fruit Bunches (EFB) is palm oil industry waste which has very large volume compared with another commodity of agro-industry waste in Indonesia. Trichoderma sp. and Larva Black Soldier Fly (BSF) with bioconversion method can be used as probelem resolve of EFB. The EFB material was obtained from Palm Oil Factory in Banten. EFB was researched in Indonesian Ornamental Fish Culture Research Institute in Depok and the result test was taken at the Laboratory of Animal Science and Technology of Bogor Agricultural University. The percentage of Trichoderma sp. fermentation (5%, 10% and 20% ) affected EFB palatability of BSF larvae and the fermented EFB with 10 % of Trichoderma sp. has a feasibility to be used as medium of BSF larvae with yield of 73.28 gram on day 4 th from the initial weight of mini larvae BSF 5 grams. At the bioconversion stage using BSF larvae with a dose of 10% Trichoderma sp. (5 gram, 15 gram and 25 gram) was obtained significant result on the initial weight of mini larvae 5 gram to 230.34 gram from fermented EFB weight of 550 gram on day 8th  , so that the average yield of average larvae was obtained By 39%. Result of proximate test of larvae on dry condition 100% obtained crude protein content (PK) 35.40 - 42.31% and crude fats (LK) 3.33 – 36.41%. Therefore, by using this test result, it will be possible to be used as poultry feed ingredient candidate in the future.